تقييم استخدامات الأراضي / تغيرات الغطاء الأرضي وتأثيرها على درجة حرارة سطح الأرض باستخدام تقنيات الاستشعار عن بعد القنيطرة نموذجًا (المغرب) - غيثة نصراوي; خالد بن الزيدية (African Journal of Advanced Pure and Applied Sciences, 2023)
This work presents a diagnosis of the effect of land use and land cover (LULC) on the Land Surface Temperature (LST) of the city of Kenitra. The study is based on determining the surface temperature variables using statistical and analytical methods to analyse satellite imagery. The study concludes that there are large areas of urban land at the expense of other land types and that a pattern of urban heat island has formed. The satellite imagery also helped to develop Normalized Difference Water Index (NDWI), Normalized Difference Vegetation Index (NDVI) and Normalized Difference Built-up Index (NDBI) maps. The study found that the built-up area increased from 29,620 hectares (3.63%) to 88,038 hectares (10.8%) over a 29-year period. Regression coefficients were observed between LST, NDVI, NDBI, and NDWI during the study period. The study showed that NDVI and NDWI were negatively associated with LST, while NDBI had a positive association with LST elevation. The study provides useful information for policymakers to use in urban management and planning.